The impact of ESG reporting on the transparency and accountability of fast fashion supply chains - Gluško, Anna (2024)
The main aim of this master’s thesis is to evaluate the current state of ESG reporting practices of selected fast fashion brands, focusing on value chain transparency through the lens of the EU’s Corporate Sustainability Due Diligence Directive (CS3D) and Corporate Sustainability Reporting Directive (CSRD). The thesis is divided into two core parts - the literature review and the main research. The literature review covers all essential theoretical background concerning sustainability, ESG reporting, and sustainability in fast fashion and delves into the significant international reporting frameworks. Further, sustainability reports of selected key fast fashion brands are examined through content analysis, focusing primarily on human rights, climate change and value chain transparency.